Folklore and Epic Traditions in Yakut Novels between Two Ages - Myreeva, Anastasiya Nikitichna (Journal of History Culture and Art Research, 2018)
The study of present-day folklore and epic traditions remains an important topic and the evolution of epic prose genres in Yakut literature serves as an evidence to this. A complete turn to the folklore and epic traditions at the new stage of evolution is typical for the genre of historical and philosophical novel. A deeper indulgence into the historical plane and much more prominent manifestations of the moral and philosophical point of views predetermined the new steps in the development of traditional poetic features and olonkho. The focus on the psychological and mental structures of the traditional cultural consciousness predefined the turn to the main source of human memory: myths, legends and olonkho. Novels written by V.S. Yakovlev-Dalan and I.M. Gogolev are prominent examples of turning to the traditional poetic features in the new stage of Yakut literature development. Thus, in their novels, written in the new stage of Yakut literature, we can see features of mythological and folklore and olonkho traditions. Folklore and epic motifs are represented in several planes and on different text levels of the epic plot: in the point of view of the author, in the stylistic features, and in the portrayal of the characters personal traits. This article examines the role of folklore and epic traditions in the process of the modern historical and philosophical novel evolution; as well as to single out the folklore and mythological motifs by implementing historical and literary analysis, typological, conceptual and geocultural methods.